591 The effects of Mineral Waters from Slănic Moldova's Spring 1 and Spring 1 bis on Fibroblast activity: An In Vitro Study (Balneo and PRM Research Journal, 2024)
Abstract: Primary fibroblast cultures obtained from Wistar rats were investigated with a focus on two vital physiological mechanisms: inflammatory processes and oxidative stress balance. These are believed to be affected by mud and sulfurous natural mineral waters, forming the fundamental biological basis for understanding the therapeutic effects of these substances. Existing scientific research highlights that various cell types, including fibroblasts, are recruited during inflammation. These cells respond to a wide array of intercellular and microenvironmental signals, leading to a regulated production of both pro- and anti-inflammatory mediators. Examples include cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and IL-6, as well as chemokines and enzymes like cyclooxygenase (COX)-2. Together, these play vital roles in modulating the inflammatory response.